In What Ways Do Natural Gestures Change Perceptions of Virtual Teamwork?. (September 2013) - Hayes, Caroline; Drew, Daniel; Clayson, Ashley; Cheng, Xuan
The goal of this study was to gain a better understanding of how gesturing over shared drawings and artifacts can change the way in which virtual team members communicate and perceive themselves as part of a team. We investigated these questions by asking pairs of traffic engineers to jointly manage traffic incidents (such as a tanker roll-over on a major highway). They communicated using a virtual collaboration interface allowing each member of the pair to communicate with his or her teammate by speaking, drawing and gesturing over a shared electronic map. We asked participant pairs to manage traffic incidents using three different versions of the interface: 1)face-to-face, where participants sat at the same table, 2)separate, where participants were positioned on opposite sides of a wall, and 3)hand images, e.g. same as 2 but with videos of the other's hands projected on the map. We found that when participants could gesture to their virtual teammates, they felt more connected and reported stronger team behaviors. Most surprisingly, stronger team behaviors were reported with hand images (#3) than face-toface. These results provide important insights for design of future virtual collaboration tools.